Designing Rh(I)-Half-Sandwich Catalysts for Alkyne [2+2+2] Cycloadditions - Orian, Laura; Bickelhaupt, F. Matthias (Synlett, 2020)
Metal-mediated [2+2+2] cycloadditions of unsaturated molecules to cyclic and polycyclic organic compounds are a versatile synthetic route affording good yields and selectivity under mild conditions. In the last two decades, in silico investigations have unveiled important details about the mechanism and the energetics of the whole catalytic cycle. Particularly, a number of computational studies address the topic of half-sandwich catalysts which, due to their structural fluxionality, have been widely employed, since the 1980s. In these organometallic species, the metal is coordinated to an aromatic ring, typically the ubiquitous cyclopentadienyl anion, C5H5–(Cp) or to the Cp moiety of a larger polycyclic aromatic ligand (Cp′). During the catalytic process, the metal continuously ‘slips’ on the ring, changing its hapticity. This phenomenon of metal slippage and its implications for the catalyst’s performance are discussed in this work, referring to the most important computational mechanistic studies reported in literature for Rh(I) half-metallocenes, with the purpose of providing hints for a rational design of this class of compounds.1 Introduction2 Mechanism of Metal-Catalyzed Acetylene [2+2+2] Cycloaddition to Benzene and the Problem of the Indenyl Effect2.1 Acetylene-Acetonitrile [2+2+2] Co-cycloaddition to 2-Methylpyridine: Evidence of the Indenyl Effect2.2 Heteroaromatic Catalysts and the Evidence of a Reverse Indenyl Effect2.3 Booth’s Mechanistic Hypothesis and the Evidence of the Indenyl Effect3 Structure–Reactivity Correlation: The Slippage-Span Model4 Conclusions and Perspectives
Keywords: alkyne [2+2+2] cycloaddition; half-sandwich catalysts; rhodium; indenyl effect; cyclopentadienyl; DFT calculations; slippage span model